A critical discourse analysis of a newspaper editorial promoting insurance - Jeyaseelan, G. (University of Jaffna, 2020)
The discourse of Insurance is constructed and disseminated as part and parcel of the modern life of people. Propaganda and awareness are always visible and universal in media and institutional communication. However, policy development and implementation standards differ from country to country, especially between developed and developing countries. This paper investigates a national newspaper editorial promoting insurance in Sri Lanka. The title of the editorial is ‘New vistas in insurance,’ which appeared on June 28, 2019, in Daily News. A linguistic approach called critical discourse analysis was used to trace general as well as ideological socio-cultural and political-economic implications covertly or overtly found in the editorial. The positions and the identities of the discourse constructor, the insurer, and the insured are unfolded using critical linguistic strategies while revealing the constructed contextual meaning or notions. The findings were that personalization strategy is used to make insurance a fundamental need to life, spiritualization makes insurance an inevitable agent to safeguard religion and religious leaders, acculturation makes insurance a part of our culture, politicization and development agentization make insurance a leader to be respected and followed. All these strategies are used in the form of the apparent altruism, contrast, transfer moves, fore- and backgrounding, assumed and asserted evaluation, emotional, ethical and logical appeals to create fear of imminent risk and relief of life-time benefits. The linguistic strategies such as nominalization, verb and voice choice, word choices for verb and noun modification, transition words contribute to the discourse strategies, especially, the discourse of insurance promotion. This study complements the need for further discourse analysis of the Sri Lankan media for their persuasion strategies in the political, economic, and socio-cultural contexts of Sri Lanka.
Keywords: Critical discourse analysis; Discourse; Insurance and media; Promotion